Motivation of Swat University Students towards learning English as a Second Language - Ali, Khurshid; Zahra, Fatima Tuz (Annals of Human and Social Sciences, 2024)
The current investigation seeks to investigate the motivation of undergraduate students at Swat University towards learning English as a foreign language. Though English is mandatory at higher education, students motivation is depending upon the monetary and financial benefits associated with the language. Conducted with 20 students from various departments, data were collected using a 20-item written questionnaire on a five-point Likert scale, along with demographic information such as age, gender, and English learning duration. The survey items were adapted from Dornyei and Csizbher (2006) and Ryan (2005). The study focused on domains including integrativeness, attitudes towards the second language community, cultural interest, attitudes towards learning English, instrumentality (promotion and prevention), and fear of assimilation. Descriptive statistics analyzed through SPSS revealed that the primary motivation for learning English was instrumental, with integrative motivation also playing a significant role. Results of the study recommend exploiting these motivational behaviours and rationalize pedagogical stratgeies.